ANALISIS TEKANAN COBLOS BAN TUBETYPE - Martina, Sufiya Putri; Sulhadi, Sulhadi; Aji, Mahardika Prasetya (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Tire is the most important part of a motor vehicle because the tires only part of a motor vehicle who have direct contact with the road . Has the sharpened spikes on the ends. So when getting a pressure , a nail will be able to penetrate the tire or tires voting . Penetration pressure of each tire has a different value because of variations in the diameter of the nail 1,25mm , 1,55mm , 1,65mm , 1,85mm , 2,05mm and 2,8mm . Retrieving data using compressive strength . The results of his research is the largest diameter 2,8mm can cast their huge tires with the pressure of 10x104 Joules. While for most small diameter 1,25mm can cast their tires with a pressure of 40x103 Joule . So, from these results it can be concluded that any spikes that have different diameters have different pressure to penetrate the tire. Keywords : Tubetype tire , Compressive Strength.